The Effectiveness of Audiovisual Media in Learning Arabic Language (Qualitative Research of Arabic Literature Students, Faculty of Letters and Arabic Language Education, Faculty of Religion, UMI) - Nurjannah Abna; Nawawi Nawawi (Tamaddun Life, 2018)
UMI Arabic language lecturers using audio-visual will be helped in learning Arabic. The development and advancement of technology provide a variety of audiovisual alternatives. The reality is that UMI lecturers generally use audiovisuals which are still limited to tapes and videos whose numbers are very limited. For this reason, in the process of learning Arabic, it needs to be great attention from lecturers in preparing teaching materials accompanied by media that can support the occurrence of active, innovative and productive learning processes, so that students not only memorize and know vocabulary but are able to apply all the vocabulary and grammar he understands in everyday conversation. This study aims to describe the effectivenessof learning Arabic with audiovisual media. This type of research is field research using a descriptive qualitative approach. The object of the research is the application of audiovisual media in learning Arabic Language students of West Asian Literature, Faculty of Literature and Students of Arabic Language Education, Faculty of Islamic Religion, University of Indonesia. Methods of collecting data with questionnaires, interviews, observation, and documentation. Data processing methods are carried out in three stages, namely preparation, data collection stage and data processing stage. The process of data analysis using data triangulation methods,namely: data reduction, data presentation, and conclusion. The three components are interrelated and carried out together in the process of concluding the final results of the study. The output that will be achieved is the publication of effective audiovisual use textbooks in learning Arabic.